Pengaruh Kepemimpinan terhadap Kinerja Karyawan Melalui Disiplin Kerja pada PT. Sebastian Jaya Metal - Putri Rahayu Permata Islami; Supardi Supardi; Agus Dharmanto (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The study aims to determine the effect of leadership on employee performance through work discipline significantly on employee performance at PT.Sebastian Jaya Metal. The approach used in this research is a quantitative approach, the sample of this study amounted to 100 employees. Data collection techniques used with questionnaire, observation and interview methods. Data analysis technique in this study uses descriptive analysis test, instrument test and hypothesis test, the result of this study indicate that leadership has a significant effect on work discipline, work discipline is significant to employee performance, leadership has a significant effect on employee performance and work discipline can mediate leadership to employee performance at PT Sebastian Jaya Metal.